Uncertainty analysis of higher-order sandwich beam using a hybrid stochastic time-domain spectral element method. Issue 5 (18th August 2020) - Sharma, Himanshu; Mukherjee, Shuvajit; Ganguli, Ranjan
Abstract: A stochastic time-domain spectral element method (STSEM) is applied to sandwich beam structures. STSEM couples the computational efficiencies of the spectral stochastic finite element method and the time-domain spectral element method. A higher-order sandwich panel theory incorporating the core flexibility is considered for the analysis. The material properties are modeled as random fields and represented by the Karhunen-Loéve expansion. The stochastic nodal displacements are expressed using the polynomial chaos expansion, and the expansion coefficients are computed by solving the spectral stochastic finite element equations. The computational efficiency of the proposed method is compared with Monte-Carlo simulation.